The origin of B-type runaway stars: Non-LTE abundances as a diagnostic - McEvoy, C; Dufton, P; Smoker, J; Lambert, D; Keenan, F; Schneider, F; de Wit, W (American Astronomical Society, 2017)
There are two accepted mechanisms to explain the origin of runaway OB-type stars: the binary supernova (SN) scenario and the cluster ejection scenario. In the former, an SN explosion within a close binary ejects the secondary star, while in the latter close multibody interactions in a dense cluster cause one or more of the stars to be ejected from the region at high velocity. Both mechanisms have the potential to affect the surface composition of the runaway star. tlusty non-LTE model atmosphere calculations have been used to determine the atmospheric parameters and the C, N, Mg, and Si abundances for a sample of B-type runaways. These same analytical tools were used by Hunter et al. for their analysis of 50 B-type open-cluster Galactic stars (i.e., nonrunaways). Effective temperatures were deduced using the Si-ionization balance technique, surface gravities from Balmer line profiles, and microturbulent velocities derived using the Si spectrum. The runaways show no obvious abundance anomalies when compared with stars in the open clusters. The runaways do show a spread in composition that almost certainly reflects the Galactic abundance gradient and a range in the birthplaces of the runaways in the Galactic disk. Since the observed Galactic abundance gradients of C, N, Mg, and Si are of a similar magnitude, the abundance ratios (e.g., N/Mg) are as obtained essentially uniform across the sample.